Adapted Grounded Group Decision Making Model - Zibarzani, Masoumeh (National Academy of Sciences India, 2015)
An integrative group decision-making method is developed to tackle the problems in arranging group decision making sessions and also use the advantage of networking hidden in a former method. Based on grounded-group decision making (GGDM), an adapted multiple criteria group-decision-making method has been used which reduces constrains and improves some shortcomings of previous one based on the social network analysis. Adapted group decision-making model (AGGDM) considers decision makers’ justification during a decision making process using the measures of social network analysis. To validate the AGGDM, a pilot study was conducted and the results were compared with GGDM. AGGDM provided accurate, integrative, and consensus-value-based results, in comparison with, traditional method of group decision making.